Efforts to Increase the Number of New Students at Jambi Vocational Schools by Implementing Digitalization Era Strategic Management - Emmelia A. Ginting; Yona Gulo; Murni Naiborhu; Irwan Susanto (Postgraduate, University of Mataram, 2025)
Increasing the number of new students in each school is very important, where the number of students is one indicator of the success of school management. Therefore, in a situation like this, what is also called strategic management is needed. Strategic management in the form of planning, organizing, action, and control are all functions of management itself that must be used to ensure the achievement of organizational goals with efficiency and effectiveness. The research design used is based on research and development and in this study only at the product design stage can produce a planning strategy to increase the number of students in SMK Jambi. The purpose of this study is to determine the implementation of strategic management applied in SMK Jambi in increasing the number of new students starting from strategy formulation, strategy implementation, and strategy evaluation. This study is a qualitative study using data collection instruments through interviews, observations, FGDs and studying documents. Data analysis was carried out using a SWOT analysis to analyze internal and external factors such as school climate, weaknesses, opportunities, and enrollment to develop a strategy to increase the number of qualified new students. The results of the SWOT analysis indicate that it is in the Strength Opportunity (SO) position, using an aggressive strategy by utilizing internal networks to pursue the goal of capturing certain opportunities from certain external networks. The recommended competitive strategies for planning educational institutions or schools are: 1) Promotion through online and offline media; 2) Holding high school/vocational school student olympiad competitions at the local level; 3) Cooperation with the local village government; 4) Teacher standards have met the qualifications of S2 graduates in their respective fields, 5) With a high fighting spirit or commitment to teaching services for teachers, 6) Facilities and infrastructure are quite complete, 7) Good cooperation with the community, 8) registration fee relief, 9) providing rewards/awards for academics who successfully register new students, ease of registration process; and 10) providing scholarship assistance to underprivileged students